Governance in sustainable public procurement : role of Supreme Audit Institution, Bangladesh - Ahammed, Kazi Forrukh (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.